Blue Beetle. Graduation day - Trujillo, Josh (DC Comics, 2023)
"Jaime Reyes has a lot to juggle. Whether it's his finals for senior year or a new villain tearing up El Paso, Jaime is always torn between two worlds. But when those worlds come crashing together at his high school graduation, nothing will ever be the same. Jaime Reyes is the hero Blue Beetle, bonded to a sentient alien artifact called a scarab that gives him high-tech armor. He's also a high school senior about to graduate! When a message from alien civilization the Reach bombards Jaime's scarab on graduation day, he's literally grounded by the Justice League. And as if that weren't enough to worry about, Jaime's parents and friends are pressuring him about his next steps in life. Jaime arrives in Palmera City to spend a gap year working in his tias' restaurant, but he's got other things on his mind- like who is the mysterious new Yellow Beetle he saw on the news? How are they connected to the Reach message that bombarded his scarab? And what's hidden here on Earth that's drawing the Reach back? Can Jaime find balance in his life and rise to become a true hero, or will this super-heroing bring the full might of the Justice League down on him?"--